2019
DOI: 10.2139/ssrn.3466022
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety: A Systematic Review

Abstract: Research in foreign language learning has notably revealed that foreign language anxiety has been a crucial area in applied linguistics. Therefore, this study tends to give a comprehensive review of literature on foreign language anxiety. This review also tries to add an additional explanation to the earlier studies of this issue. It clarifies the concept of foreign language anxiety and how it is different from other related types of anxiety. Finally, it shows the main causes and effects of foreign language an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…From the data, it was revealed that the rationale of this factor is the students' unpreparedness for the response of answering questions that will be given either by the teacher or friends in class. This is in line with the results of some previous studies, such as Asysyfa et al, (2019), Naser & Nijr (2019), Taqwa, et al, (2022) and Zakiya, et al, (2022 which highlighted that speaking anxiety is caused by fear of evaluation from other people. Therefore, the fear of making mistakes is something that really hinders EFL students to speak and to respond to questions.…”
Section: Questionssupporting
confidence: 92%
“…From the data, it was revealed that the rationale of this factor is the students' unpreparedness for the response of answering questions that will be given either by the teacher or friends in class. This is in line with the results of some previous studies, such as Asysyfa et al, (2019), Naser & Nijr (2019), Taqwa, et al, (2022) and Zakiya, et al, (2022 which highlighted that speaking anxiety is caused by fear of evaluation from other people. Therefore, the fear of making mistakes is something that really hinders EFL students to speak and to respond to questions.…”
Section: Questionssupporting
confidence: 92%
“…Kecemasan berbahasa asing merupakan reaksi emosional, perasaan cemas, stres, gugup, ketakutan, jantung berdebar-debar, kehilangan konsentrasi, dan kekhawatiran yang berkaitan dengan pembelajaran bahasa asing [18], [19]. Kecemasan berbahasa asing termasuk ke dalam jenis kecemasan situasi-spesifik.…”
Section: Pendahuluanunclassified
“…Jadi fokusnya adalah kekhawatiran yang dialami para peserta didik yang belajar bahasa Inggris sebagai bahasa asing pada sa'at terjadi perubahan cara belajar ke sistim belajar daring. Akibat yang ditimbulkan dari kekhawatiran ini ada dua yaitu debilitating (harmful) anxiety and facilitating (helpful) anxiety (Naser Oteir & Nijr Al-Otaibi, 2019). Lebih lanjut Naser, et al menjelaskan bahwa debilitating (harmful) anxiety adalah kekhawatiran yang bersifat merugikan peserta didik karena berakibat negatip pada hasil pembelajarannya.…”
Section: "Tak Sedikit Pelajar Yang Tidak Serius Menjalani Perkuliahan...unclassified